Long-term outcomes after adjuvant treatment of sequential versus combination docetaxel with doxorubicin and cyclophosphamide in node-positive breast cancer: BCIRG-005 randomized trial. - Mackey, J.; Pienkowski, T.; Crown, J.; Sadeghi, S.; Martin, M.; Chan, Arlene; Saleh, M.; Sehdev, S.; Provencher, L.; Semiglazov, V.; Press, M.; Sauter, G.; et al. (Oxford University Press, 2016)
BACKGROUND: The optimal regimen for adjuvant breast cancer chemotherapy is undefined. We compared sequential to concurrent combination of doxorubicin and cyclophosphamide with docetaxel chemotherapy in women with node-positive non-metastatic breast cancer. We report the final, 10-year analysis of disease-free survival (DFS), overall survival (OS), and long-term safety. PATIENTS AND METHODS: A total of 3298 women with HER2 nonamplified breast cancer were randomized to doxorubicin and cyclophosphamide every 3 weeks for four cycles followed by docetaxel (AC ? T) every 3 weeks for four cycles or docetaxel, doxorubicin, and cyclophosphamide (TAC) every 3 weeks for six cycles. The patients received standard radiotherapy and endocrine therapy and were followed up for 10 years with annual clinical evaluation and mammography. RESULTS: The 10-year DFS rates were 66.5% in the AC ? T arm and 66.3% in the TAC arm (P = 0.749). OS was 79.9% in the AC ? T arm and 78.9% in the TAC arm (P = 0.506). TAC was associated with higher rates of febrile neutropenia, although G-CSF primary prophylaxis greatly reduced this risk. AC ? T was associated with a higher rate of myalgia, hand-foot syndrome, fluid retention, and sensory neuropathy. CONCLUSION: This 10-year analysis of the BCIRG-005 trial confirmed that the efficacy of TAC was not superior to AC ? T in women with node-positive early breast cancer. The toxicity profiles differ between arms and were consistent with previous reports. The TAC regimen with G-CSF support provides shorter adjuvant treatment duration with less toxicity. TRIAL REGISTRATION: ClinicalTrials.gov Identifier NCT00312208.